2018
DOI: 10.1021/acs.est.7b06327
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated Polyfluorinated Ether Sulfonates Exhibit Higher Activity toward Peroxisome Proliferator-Activated Receptors Signaling Pathways than Perfluorooctanesulfonate

Abstract: Chlorinated polyfluorinated ether sulfonates (Cl-PFAESs) are the alternative products of perfluorooctanesulfonate (PFOS) in the metal plating industry in China. The similarity in chemical structures between Cl-PFAESs and PFOS makes it reasonable to assume they possess similar biological activities. In the present study, we investigated whether Cl-PFAESs could induce cellular effects through peroxisome proliferator-activated receptors (PPARs) signaling pathways like PFOS. By using fluorescence competitive bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(83 citation statements)
references
References 50 publications
4
79
0
Order By: Relevance
“…The protein binding properties of PFASs are key contributors to their bioaccumulation as well as to their biological effects on organisms. , A higher binding affinity to human liver fatty acid-binding protein for 6:2 Cl-PFESA compared to PFOS was reported in our previous study, which may lead to a more serious accumulation of 6:2 Cl-PFESA in the liver . Li et al reported tighter binding of 6:2 Cl-PFESA to peroxisome proliferator-activated receptors (PPARs) compared to that of PFOS, which was explained by the stronger activation of the PPAR pathways . Xin et al also observed a stronger binding potency for 6:2 Cl-PFESA than for PFOS to thyroid hormone transport proteins and a similar agonistic activity toward thyroid hormone receptors …”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The protein binding properties of PFASs are key contributors to their bioaccumulation as well as to their biological effects on organisms. , A higher binding affinity to human liver fatty acid-binding protein for 6:2 Cl-PFESA compared to PFOS was reported in our previous study, which may lead to a more serious accumulation of 6:2 Cl-PFESA in the liver . Li et al reported tighter binding of 6:2 Cl-PFESA to peroxisome proliferator-activated receptors (PPARs) compared to that of PFOS, which was explained by the stronger activation of the PPAR pathways . Xin et al also observed a stronger binding potency for 6:2 Cl-PFESA than for PFOS to thyroid hormone transport proteins and a similar agonistic activity toward thyroid hormone receptors …”
Section: Discussionmentioning
confidence: 60%
“…23 Li et al reported tighter binding of 6:2 Cl-PFESA to peroxisome proliferator-activated receptors (PPARs) compared to that of PFOS, which was explained by the stronger activation of the PPAR pathways. 48 Xin et al also observed a stronger binding potency for 6:2 Cl-PFESA than for PFOS to thyroid hormone transport proteins and a similar agonistic activity toward thyroid hormone receptors. 49 The binding parameters of PFOS to HSA have been reported in several studies.…”
Section: ■ Discussionmentioning
confidence: 92%
“…Specifically, perfluorobutanesulfonic acid (PFBS) used as a substituent for perfluorooctanesulfonic acid (PFOA) was demonstrated to be a proadipogenic agent, promoting the differentiation of 3T3-L1 preadipocytes to adipocytes by up-regulating PPARγ and C/EBPα transcription factors and lipogenic acetyl-CoA carboxylase (ACC) and fatty acid synthase (FAS) [51]. In comparison to PFOS, chlorinated polyfluorinated ether sulfonates (Cl-PFAESs) were shown to be more potent stimulators of 3T3-L1 adipogenesis through the PPARγ pathway [52]. Perfluorinated alkyl acids (PFAAs) are also capable of inducing adipogenesis in 3T3-L1 cells at human blood-based exposure levels [53].…”
Section: Perfluorinated Compoundsmentioning
confidence: 99%
“…Peroxisome proliferator activator receptor gamma (PPARγ) is a member of nuclear receptor family that plays versatile roles in human physiology. , In the recent decade, transactivation of PPARγ has been found to be related to human fatty liver disease and endocrine-disrupting effects including undermined osteogenesis, promoted adipogenesis, and increased tendency toward later-life obesity. PPARγ agonist activity of chemicals thus serves as an early indicator of the adverse health effects. Many chemicals such as organotins, phthalate esters, chlorinated polyfluorinated ether sulfonates, and brominated and organo-phosphorus flame retardants have been reported as PPARγ agonists in in vitro assays. , However, in vitro assays are time-consuming and expensive, thus not suitable for screening of the huge amount of environmental chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Many chemicals such as organotins, phthalate esters, chlorinated polyfluorinated ether sulfonates, and brominated and organo-phosphorus flame retardants have been reported as PPARγ agonists in in vitro assays. [6][7][8][9][10][11][12][13]4 However, in vitro assays are time-consuming and expensive, thus not suitable for screening of the huge amount of environmental chemicals.…”
Section: ■ Introductionmentioning
confidence: 99%